2013
DOI: 10.1016/j.asd.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cardiac ganglion in the crab Neohelice granulata and immunohistochemical evidence of GABA-like extrinsic regulation

Abstract: Please cite this article as: Yang,, M., Carbó Tano,, M., Freudenthal,, R., Hermitte,, G., Characterization of the cardiac ganglion in the crab Neohelice granulata and immunohistochemical evidence of GABAlike extrinsic regulation, Arthropod Structure and Development (2012), doi: 10.1016/j.asd.2012 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(44 reference statements)
2
4
0
Order By: Relevance
“…In our previous work in the crab Neohelice, immunohistochemical techniques have allowed us to identify GABA-like immunoreactive processes entering the heart, which later branched in slender and varicose fibers forming a network around the somas of large neurons of the cardiac ganglion. These results strengthen the idea that GABA has a role in the peripheral inhibition of the cardiac system [59].…”
Section: Introductionsupporting
confidence: 87%
“…In our previous work in the crab Neohelice, immunohistochemical techniques have allowed us to identify GABA-like immunoreactive processes entering the heart, which later branched in slender and varicose fibers forming a network around the somas of large neurons of the cardiac ganglion. These results strengthen the idea that GABA has a role in the peripheral inhibition of the cardiac system [59].…”
Section: Introductionsupporting
confidence: 87%
“…Although the CG contains just nine neurons, its stereotyped neuronal output is both flexible and robust (Cooke, 2002; Cruz-Bermúdez & Marder, 2007; Lane et al, 2016; Tazaki & Cooke, 1979). The physiological response of the crustacean cardiac ganglion to various neuromodulators has been well characterized in a variety of species (Cruz-Bermúdez & Marder, 2007; Dickinson et al, 2015; Lane et al, 2018; Yang et al, 2013). In addition to hormonal modulation, the CG is modulated extrinsically by at least three pairs of input nerves (Alexandrowicz, 1934).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry studies have visualized some modulatory inputs in whole-mount preparations of CGs in various species. Extensive GABA-like projections are found throughout the CG of the lobster P. argus (Delgado et al, 2000; Yang et al, 2013), and nitrous oxide synthase-like immunoreactivity is found in posterior motor neurons and small pacemaker cells of the crab C. productus (Scholz et al, 2002). Recent work has used MALDI imaging to characterize the distribution of neuropeptides in the cardiac ganglion of C. borealis , and confirmed 316 unique neuropeptides including those studied here (DeLaney & Li, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although the CG contains just nine neurons, its stereotyped neuronal output is both flexible and robust ( Cooke, 2002 ; Cruz-Bermúdez & Marder, 2007 ; Lane et al, 2016 ; Tazaki & Cooke, 1979 ). The physiological response of the crustacean CG to various neuromodulators has been characterized in a variety of species ( Cruz-Bermúdez & Marder, 2007 ; Dickinson et al, 2015 ; Lane et al, 2018 ; Yang et al, 2013 ). In addition to hormonal modulation, the CG is modulated extrinsically by at least three pairs of input nerves ( Alexandrowicz, 1934 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry studies have visualized some modulatory inputs in whole-mount preparations of CGs in various species. Extensive GABA-like projections are found throughout the CG of the lobster Panularis argus ( Delgado et al, 2000 ; Yang et al, 2013 ), and nitric oxide synthase-like immunoreactivity is found in posterior LC and small pacemaker cells of the crab Cancer productus ( Scholz et al, 2002 ). Recent work has used MALDI imaging to characterize the distribution of neuropeptides in Cancer borealis and confirmed 316 unique neuropeptides including those studied here ( DeLaney & Li, 2020 ).…”
Section: Introductionmentioning
confidence: 99%